Electro-discharge machining of Ti-6AI-4V alloy using Cu-TaC compact electrode with urea dielectric: Reactions and their effects on the machined surface - Ndaliman, Mohammed Baba; Khan, Ahsan Ali; Lafia-Araga, Ruth Anayimi (IEEE, 2017)
This paper presents the investigation of compounds / phases formed during the Electrical Discharge Machining (EDM) of titanium alloy (Ti-6AI-4V) with Cu-TaC compact electrode using urea dielectric fluid. It is proposed that the materials involved in the machining are likely to react and form new compounds on the EDMed surface. The outcomes of the reactions were predicted. The EDMed surfaces were subjected to energy dispersive X-ray spectroscopy (ED X) and X-ray diffraction (XRD) analysis to determine the changes in the surface composition. Results of EDX analysis indicate the presence of additional elements (Cu, Ta, 0 and C) on the surface of the parent alloy. XRD results also confirm the main compounds formed on the surface to include metallic oxides, carbides and nitrides (TaC, TiC, Ti1N, TiD) of tantalum and titanium. It is concluded that the surface was reinforced during the EDM with hardened ceramic layers which are capable of enhancing its wear properties.